The industry of Pension Fund Administrators in Honduras (Journal of Management & Business, 2023)
The objective of this paper is to analyze the Pension Fund Administrators (AFP) industry in Honduras and its impact on the economic system and the Economically Active Population (EAP) of the country. To carry out this research, a cross-sectional approach was used, using bibliographic sources and statistical data from Honduran governmental entities. The study focuses on examining the data provided by these governmental institutions to analyze the economic behavior generated by the PFAs. The results reveal a growth in investments and in the generation of employment for the EAP, indicating a positive impact on the country’s economy.
Keywords: Economically Active Population; Pension Fund Administrators; Investment